Haploidentical versus unrelated allogeneic stem cell transplantation for relapsed/ refractory acute myeloid leukemia: A report on 1578 patients from the Acute leukemia working party of the EBMT - Brissot, Eolia; Labopin, Myriam; Ehninger, Gerhard; Stelljes, Matthias; Brecht, Arne; Ganser, Arnold; Tischer, Johanna; Kroeger, Nicolaus; Afanasyev, Boris; Finke, Juergen; Elmaagacli, Ahmet; Einsele, Herman; et al. (Haematologica, 2019)
Primary refractory or relapsed acute myeloid leukemia is associated with a dismal prognosis. Allogeneic stem cell transplantation is the only therapeutic option that offers prolonged survival and cure in this setting. In the absence of a matched sibling donor, transplantation from unrelated 10/10 HLA allele-matched or 9/10 HLA allele-mismatched donors and haploidentical donors are potential alternatives. The current study aimed to compare the outcomes of acute myeloid leukemia patients with active disease who received allogeneic stem cell transplantation from a haploidentical donor with post-transplant cyclophosphamide (n=199) versus an unrelated 10/10-matched donor (n=1111) and versus an unrelated 9/10-mismatched donor (n=383) between 2007 and 2014 and who were reported to the European Society for Blood and Marrow Transplantation registry. Propensity score weighted analysis was conducted in order to control for disease risk imbalances between the groups. The leukemia-free survival rates at 2 years of recipients of grafts from a haploidentical donor, an unrelated 10/10-matched donor and an unrelated 9/10-mismatched donor were 22.8%, 28% and 22.2%, respectively (P=NS). In multivariate analysis, there were no significant differences in leukemia-free survival, overall survival, relapse incidence, non-relapse mortality, or graft-versus-host-disease-free relapse-free survival between the three groups. Two predictive factors were associated with a higher relapse incidence: transplantation during first or second relapse compared to primary refractory acute myeloid leukemia and poor cytogenetics. Allogeneic stem cell transplantation may rescue about 25% of acute myeloid leukemia patients with active disease. Importantly, the outcomes of transplants from haploidentical donors were comparable to those from 10/10-matched and 9/10-mismatched unrelated donors. Therefore, a haploidentical donor is a valid option for acute myeloid leukemia patients with active disease.
CRIS-Team Scopus Importer:2023-03-23